Chemo-mechanical model for skeletal muscle contraction - Karami, M.; Calvo, B.; Zohor, H.; Firoozbakhsh, H.; Grasa, J. (Jornada de Jóvenes Investigadores del I3A, 2017)
Generation of force in skeletal muscle tissue depends on both chemical and mechanical phenomena. In this work, considering the kinetics of cross bridges, a one dimensional model has been proposed for predicting the isometric force according to the intracellular calcium ion distribution.